Professional Identity Development of Online Counselors: Voices from Teletherapy Platforms - Faida, Eka Wilda; Wahyuni, Titin; Masyfufah, Lilis (Yayasan Minang Darussalam, 2025)
Background. The rapid growth of teletherapy platforms has redefined counseling practices, requiring counselors to negotiate new roles, boundaries, and self-concepts. Professional identity development in online counseling is shaped by unique digital interactions, technological mediation, and evolving client expectations, yet empirical insights into this phenomenon remain limited. Purpose. This qualitative study aimed to explore how online counselors construct and experience their professional identity within teletherapy platforms. Specifically, it examined the factors that influence their sense of competence, role boundaries, ethical awareness, and connection with clients in a virtual counseling environment. Method. The study involved 25 licensed counselors from diverse backgrounds who actively deliver counseling services through major teletherapy platforms. Data were collected through in-depth semi-structured interviews and analyzed thematically using an interpretive phenomenological approach. Results. The study involved 25 licensed counselors from diverse backgrounds who actively deliver counseling services through major teletherapy platforms. Data were collected through in-depth semi-structured interviews and analyzed thematically using an interpretive phenomenological approach. Conclusion. The findings revealed that online counselors experience identity development as a dynamic process characterized by adaptation to digital tools, redefinition of the counselor-client relationship, and negotiation of ethical standards in a virtual context. Key themes included increased flexibility and reach, feelings of isolation from professional communities, the need for continuous digital literacy, and tensions between traditional counseling norms and platform-driven practices.